MODEL KETERKAITAN VARIABEL TRUST IN BRAND TERHADAP BRAND LOYALITY MELALUI REINFORCES COMMITMENT (Studi Kasus Pada Perusahaan Semen PT. Holcim Indonesia Jawa Timur ) - kartika, chandra (Majalah Ekonomi, 2016)
ABSTRACT This study aims to provide most of the answers to the problems of the interrelationships customers Trust In Brand dimension given to the Manufacturing Company, due to the manner of observation and measurement beyond the more value-value that fell on the dimensions of Trust In Brand in Cement Company PT. Holcim Indonesia, a growing number of complaints arising from its customers about the relationship of trust acquired customers decreased, so the loyalty level pelangganpun influence, therefore the researchers will examine the issue very krausal to increase the level of relationship Trust In Brand and to increase the value of loyalty and through commitment to customers, mainly in manufacturing companies precisely in PT. Holcim Indonesia and will examine the influence of Trust In Brand to influence brand loyalty through Reinforces Commitment. Samples in this study of 144 respondents drawn from the Customer associated with cement products from 2 cities research has been determined in the study of Surabaya and Malang. This study used quantitative analysis and qualitative approaches analysis method using the analysis technique SEM amous versions of 20:00 on a findings are expected to be found positive results and can describe the level of Trust In Brand is further improved and certainty in order to help improve the level of Trust In Brand against Brand Customer Loyalty through Reinforces Commitment to the Cement Manufacturing Company PT. Holcim Indonesia. Key Word : Trush In Brand, Brand Loyality, Reinforces Commitment